Webinar Sosialisasi Covid-19 Dan Isolasi Mandiri Via Zoom Di Desa Pesanggrahan Kecamatan Solear Kabupaten Tangerang - Dewi, Ratna Sari; Kenvisyah, Zahran Hafiidh (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2021)
Community service is one of the Tri Dharma of Higher Education in order to involve universities to solve problems that exist in the community, one of which is through student work activities (KKM). The increasing trend of COVID-19 virus cases in Indonesia has resulted in this year's KKM activities being carried out online. COVID-19 is a pandemic outbreak that has hit various countries and is a form of concern for the public. Currently, there are many variants of the COVID-19 outbreak mutation that result in an increased risk of spread. Many health facilities in Indonesia are currently at full capacity, so people who experience mild COVID-19 symptoms are directed to undergo independent isolation at their respective homes. The 37 UNTIRTA Thematic KKM group held a webinar work program on COVID-19 socialization and self-isolation. The conclusion of this activity is the implementation of a COVID-19 webinar and self-isolation targeting the general public with a speaker from dr. Taufik Nugraha, Doctor of the Cikuya Health Center and the presence of representatives of Pasanggrahan Village and the Sub-district Head of Solear. The purpose of this work program is to educate the general public regarding COVID-19 and the procedures for proper self-isolation. The results of the webinar have provided additional understanding to the community, especially the residents of Pesanggrahan Village, Solear District, Tangerang Regency. It is recommended that village government officials do not get bored educating their people about Covid 19.